The War Veteran Identity - Marković Savić, Olivera S. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
The paper discusses how war veterans perceive themselves and how they answer the question "Who am I?". War veterans face many challenges in the process of re-socialization from a state of war and war traumatization to a peacetime society. There are several reasons why their re-socialization is a slow process: the first one is that a war engagement is in itself a highly stressful situation which carries traumas of different degrees, the other reason is the changed system of values ​​in relation to war engagement. Namely, at the time they went to war, they had a strong social support, but at the time of their return and today this support is lost to the point of judgment. And the third reason which limits their re-socialization is the situation of social transition they found on their return from war, which specifically means that a large percentage of the population in general, and thus the war veterans after returning from the war, lost their jobs, creating a large social group of "transition losers". Such a condition often generates an identity crisis. This set of socio-cultural circumstances together with the ontological insecurity carried by war trauma generate an identity crisis, which is manifested among the respondents in nihilistic answers when responding to questions about their own personality. Studying the identity of war veterans, it was found that a strong attachment to the veteran identity is dominant. In fact, this paper discusses the different ways in which this attachment is refracted in the personality and identity of subjects, from negative attitudes to the pride in belonging to a group of war veterans and personal fulfillment in the activism in associations of war participants.